Toward Numerical Modeling of Interactions Between Ice-Marginal Proglacial Lakes and Glaciers - Carrivick, Jonathan L.; Tweed, Fiona S.; Sutherland, Jenna L.; Mallalieu, Joseph (Frontiers in Earth Science, 2020)
Global climate change is evidently manifest in disappearing mountain glaciers and receding and thinning ice sheet margins. Concern about contemporaneous proglacial lake development has spurred an emerging area of research seeking to quantitatively understand lake - glacier interactions. This perspectives article identifies spatio-temporal disparity between the coverage of field data, remote sensing observations and numerical modeling efforts. Throughout, an overview of the physical effects of lakes on glaciers and on ice sheet margins is provided, drawing evidence together from very recent and high-impact studies of both modern glaciology and of the Quaternary record. We identify and discuss six challenges for numerical modeling of lake - glacier interactions, namely that there are meltwater exchanges between glaciers and ice-marginal lakes, lake bathymetry and glacier bed topography are often unknown, lake - glacier interactions affect the longitudinal stress regime of glaciers, lake water temperature affects glacier melting but is very poorly constrained, the interactions persist with considerable spatio-temporal variability and with boundary migration, and data for model parameterization and validation is extremely scarce. Overall, we contend that numerical modeling is a key frontier in the cryospheric sciences to deliver process understanding of lake - glacier interactions.